Comparison of Patients Receiving Long-Term Metformin Therapy and Vitamin B12 Monitoring. (August 2015) - Farland, Michelle Z.; McPheeters, Chelsey M.; Renwick, Rachel C.; Barlow, Patrick B.; Williams, Juli D.; Keeble, Donald S.; Franks, Andrea S.
Background: Metformin may cause vitamin B12 deficiency that can present with symptoms of peripheral neuropathy. Lack of vitamin B12 serum concentration monitoring could result in vitamin B12 deficiency progression, worsening of symptoms, and unnecessary medication.Objectives: The purpose of this study was to ( a ) compare the influence of the rate of symptoms consistent with vitamin B12 deficiency on obtaining vitamin B12 serum concentrations in patients using metformin; ( b ) assess if vitamin B12 serum concentrations were ordered as a routine monitoring parameter.Methods: This retrospective case–control study evaluated patients receiving metformin. Patients in the case group had documented symptoms or diagnosis of peripheral neuropathy or macrocytic anemia, while those in the control group did not. The primary outcome was frequency of vitamin B12 serum concentration assessment. The secondary outcomes included frequency of vitamin B12 serum concentration assessment for patients presenting with symptoms or diagnosis of peripheral neuropathy or macrocytic anemia.Results: Analysis included 355 patients (116 cases, 239 controls). The cases were 5 times more likely to have a serum vitamin B12 serum concentrations drawn versus controls (odds ratio [OR] = 5.83, 95% confidence interval [CI] = 3.47-9.77, P < .001). Patients with a diagnosis of peripheral neuropathy or macrocytic anemia were 4 times more likely to have a serum vitamin B12 concentration drawn than those who did not (peripheral neuropathy: OR = 4.92, 95% CI = 2.95-8.21, P < .001; macrocytic anemia: OR = 5.41, 95% CI = 1.30-20.97, P = .007).Conclusions: Cases were more likely to have vitamin B12 serum concentrations assessed than patients without symptoms. The majority of patients taking metformin did not have routine vitamin B12 serum concentration assessments for medication adverse event monitoring.